Composition, antimicrobial and antioxidant activity of Artemisia herba-alba essential oil from northeast Algeria (Khenchela region) - Kadri Mounira; Mouane Aicha; Goubi Sana; Ramdan Farah; Yahia Abdelouhab (Acta Periodica Technologica, 2023)
Plants are traditionally utilized in Algeria to treat many disorders, such as Artemisia herba-alba (Asteraceae family), which is a North African species. In Algeria, it is characterized by an excellent fodder fee and by a composition of essential oils having antiseptic, vermifuge, and antispasmodic properties. The present study aims to investigate the antioxidant and antimicrobial activities and chemical composition of the essential oil of Artemisia herba-alba found in northeast Algeria (Khenchela region). Artemisia herba-alba essential oil was extracted by hydrodistillation and its chemical composition was identified by GC/MS. In addition, the antioxidant activity of the extracted essential oil was determined using the DPPH assay. The agar disc diffusion method was used to determine how well the essential oil killed germs. The essential oil was analyzed by GC/MS, revealing 35 constituents, of which the major ones were identified as Thujone (10.55%), borneol (5.98%), and eucalyptol (1.63%). The observed IC50 values for the DPPH assay were 18.44 ± 0.006 mg/mL. On the other hand, this oil proved effective against all tested strains in the 22.67 ± 3.215 mm range, including Listeria innocua CIP 74915.